PERAN ORANG TUA DALAM PENCEGAHAN ANAK KECANDUAN GADGET DENGAN POLA ASUH DI ERA DIGITAL - Surachman, Surachman; Safira, Ratu Sella; Layyinah, Layyinah; Susanti, Lis; Masulah, Masulah (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
Today's children, especially school students, really need the internet to complete their schoolwork. If children are free to access the internet without parental supervision, it can have fatal consequences. This condition will certainly be even more worrying because gadgets will eventually replace the social role of children that they should do, such as interacting with parents, friends, the environment, and creativity in the real world. In addition, gadgets canconnect them to the world of violence, disturbances, and negative shows. Various challengin affect children's minds, make them addicted, and are very likely to connect them to the world of violence, disturbances, and negative shows. Various challenging conditions faced by these children, community service activities are carried out, with the aim of educating parents so that they can make the right efforts in caring for and educating children in this digital era. This community service is carried out by providing educational materials (parenting) to parents under the guidance of the Gober PAUD Kasih Ibu in Serang Districk.